Effects of motor imagery training on generalization and retention for different task difficulties - Sato, Yoichiro (Frontiers in Human Neuroscience, 2024)
Although previous studies have suggested that motor adaptation through motor imagery training of similar tasks can improve retention and generalization of motor learning, the benefits of mental and physical training remain unclear for different task difficulties. Two experiments were conducted in this study. The first experiment aimed to determine whether there were differences in movement time (MT) when drawing circles based on three conditions in accordance with Fitts' law. The results showed significant differences in MT among the three conditions (p < 0.001), with MT becoming long as the width of the circle line (which indicated different difficulty level) narrowed. The second experiment aimed to determine whether the task difficulty influenced immediate generalization and retention at 24 h after mental vs. physical training. Participants in both training groups practiced the task with the medium-sized circle, which indicated medium difficulty. The posttest results revealed that mental training leads to considerable performance improvement than physical training, as demonstrated by a shorter MT regardless of the task difficulty level. Meanwhile, the retention test results showed no difference in generalization between mental and physical training. However, generalization of an easier task was more effectively retained than more difficult tasks. These results suggest that mental training can improve performance during the adaptation phase and that difficulty level can influence the degree of retention.